Nasal sound pressure as objective verification of implant in active transcutaneous bone conduction devices - Reinfeldt, Sabine; Rigato, Cristina; Håkansson, Bo; Fredén Jansson, Karl-Johan; Eeg-Olofsson, Måns (Medical devices (Auckland, N.Z.), 2019)
Active transcutaneous bone conduction devices consist of an external audio processor and an internal implant under intact skin. During the surgical procedure, it is important to verify the functionality of the implant before the surgical wound is closed. In a clinical study with the new bone conduction implant (BCI), the functionality of the implant was tested with an electric transmission test, where the output was the nasal sound pressure (NSP) recorded in the ipsilateral nostril. The same measurement was performed in all follow-up visits to monitor the implant's functionality and transmission to bone over time. The objective of this study was to investigate the validity of the NSP method as a tool to objectively verify the implant's performance intraoperatively, as well as to follow-up the implant's performance over time. Thirteen patients with the BCI were included, and the NSP measurement was part of the clinical study protocol. The implant was electrically stimulated with an amplitude-modulated signal generator using a swept sine 0.1-10 kHz. The NSP was measured with a probe tube microphone in the ipsilateral nostril. The NSP during surgery was above the noise floor for most patients within the frequency interval 0.4-5 kHz, showing NSP values for expected normal transmission of a functioning implant. Inter-subject comparison showed large variability, but follow-up results showed only minor variability within each subject. Further investigation showed that the NSP was stable over time. The NSP method is considered applicable to verify the implant's functionality during and after surgery. Such a method is important for implantable devices, but should be simplified and clinically adapted. Large variations between subjects were found, as well as smaller variability in intra-subject comparisons. As the NSP was found to not change significantly over time, stable transmission to bone, and implant functionality, were indicated.